DAMPAK KENAIKAN HARGA BBM TERHADAP KINERJA EKONOMI MAKRO, KERAGAAN EKONOMI SEKTORAL DAN RUMAHTANGGA DI INDONESIA (Suatu Pendekatan Model Ekonomi Keseimbangan Umum Recursive Dynamic) - Rina Oktaviani; Sahara Sahara (Jurnal Manajemen & Agribisnis, 2005)
An 29% increased on fuel price on  March 1st, 2005 has several implications on Indonesian economy. It includes micro and macroeconomics performance of Indonesian economy.  Using Recursive Dynamic Computable General Equilibrium (CGE) Model, namely “Poverty Indonesian Model”, the simulations show that an increase of fuel price tends to reduced household and industry demand for fuel (oil refinery). Reducing demand also happen although an increase of fuel price following which the compensation fund on health and education sectors. Furthermore, wage of unskilled labor also decline. The purchasing power and welfare of households will be reduced because the households also face the increasing prices of commodities. From Macroeconomic side, an increased of fuel price decline has no significant impact on GDP and decline a household consumption and land rent. The inflation rate will around 3% after and before compensation program.